Wadon Wadas: The Wadas Women's Movement Against the Quarry An Ecofeminism Study - Robingah Robingah; Jun Firmansyah (International Journal Multidisciplinary Science, 2025)
When exploitation, capitalization, or land conversion occurs, it will certainly lead to conflicts between local communities and the private/government or even the State. Damage to nature due to exploitation and land conversion has a negative impact on women's bodies and their lives. Wadas is a village located in Bener sub-district, Purworejo, Central Java. The name Wadas has been widely discussed due to the discourse of andesite/quarry stone mining in the village. The quarry stone is the raw material for the construction of the Bener dam, one of President Jokowi's National Strategic Projects. The purpose of this research is to analyze the factors of resistance carried out by the Wadon Wadas movement, a movement carried out by Wadas women as a form of resistance to mining in their village, and to analyze the forms of resistance undertaken. The method used is descriptive. Data was obtained using documentation techniques, through news in digital media and social media. To find out the forms of resistance, the authors use James C. Scott's resistance theory. The finding was that Wadon Wadas applied a structured, observable form of open resistance to defend their land.